On Bootstrap Methods in Orthogonal Regression Model - Abdullah, Mokhtar (Universiti Putra Malaysia Press, 1995)
This paper discusses the nonparametric bootstrap method for evaluating the standard errors of the parameter estimates of orthogonal regression. The percentile, bias-corrected, the bias-corrected and accelerated (BCA) , and the calibrated or iterated BCA method were considered for confidence intervals for the parameters of the model. Based on simulation studies, it was found that the iterated BCA method produced a more reliable confidence interval than the other methods.